Skin PAMPA: Application in practice - Bálint Sinkó; Gábor Vizserálek; Krisztina Takács-Novák (International Association of Physical Chemists (IAPC), 2015)
Transdermal drug delivery has been growing extensively in the past decades, therefore new, reliable and cost-effective in vitro models were demanded to support the research and development on this field. Model membrane of PAMPA mimicking skin penetration was first described in 2006, but the need for more bio-mimetic system has been arisen by new industrial tendencies and a bio-relevant system was published in 2012. Since its first publication Skin PAMPA has already been applied by several universities and industrial groups successfully and the first articles, podium and poster presentations have been appeared. The original Skin PAMPA model has been further developed in order to extend its application for formulations. Examples of liquid or semi-solid formulation projects and transdermal patch studies are available beside standard solution applications. The present review demonstrates the different approaches needed for various type of samples, provides examples of applications and practical conclusions for further improvement.